Accelerated Biodegradation of Veterinary Antibiotics in Agricultural Soil following Long‐Term Exposure, and Isolation of a Sulfamethazine‐degrading Microbacterium sp. Issue 1 (1st January 2013) - Topp, Edward; Chapman, Ralph; Devers‐Lamrani, Marion; Hartmann, Alain; Marti, Romain; Martin‐Laurent, Fabrice; Sabourin, Lyne; Scott, Andrew; Sumarah, Mark
Abstract : The World Health Organization has identified antibiotic resistance as one of the top three threats to global health. There is concern that the use of antibiotics as growth promoting agents in livestock production contributes to the increasingly problematic development of antibiotic resistance. Many antibiotics are excreted at high rates, and the land application of animal manures represents a significant source of environmental exposure to these agents. To evaluate the long‐term effects of antibiotic exposure on soil microbial populations, a series of field plots were established in 1999 that have since received annual applications of a mixture of sulfamethazine (SMZ), tylosin (TYL), and chlortetracycline (CTC). During the first 6 yr (1999–2004) soils were treated at concentrations of 0, 0.01 0.1, and 1.0 mg kg −1 soil, in subsequent years at concentrations of 0, 0.1, 1.0, and 10 mg kg −1 soil. The lower end of this concentration range is within that which would result from an annual application of manure from medicated swine. Following ten annual applications, the fate of the drugs in the soil was evaluated. Residues of SMZ and TYL, but not CTC were removed much more rapidly in soil with a history of exposure to 10 mg/kg drugs than in untreated control soil. Residues of 14 C‐SMZ were rapidly and thoroughly mineralized to 14 CO2 in the historically treated soils, but not in the untreated soil. A SMZ‐degrading Microbacterium sp. was isolated from the treated soil. Overall, these results indicate that soil bacteria adapt to long‐term exposure to some veterinary antibiotics resulting in sharply reduced persistence. Accelerated biodegradation of antibiotics in matrices exposed to agricultural, wastewater, or pharmaceutical manufacturing effluents would attenuate environmental exposure to antibiotics, and merits investigation in the context of assessing potential risks of antibiotic resistance development in environmental matrices.